Identification of bi-allelic KIF9 loss-of-function variants contributing to asthenospermia and male infertility in two Chinese families - Meng, Zhixiang; Meng, Qingxia; Gao, Tingting; Zhou, Hui; Xue, Jiajia; Li, Hong; Wu, Yibo; Lv, Jinxing (Frontiers in Endocrinology, 2023)
Asthenozoospermia (AZS) is a leading cause of male infertility, affecting an estimated 18% of infertile patients. Kinesin proteins function as molecular motors capable of moving along microtubules. The highly conserved kinesin family member 9 (KIF9) localizes to the central microtubule pair in the flagella of Chlamydomonas cells. The loss of KIF9 expression in mice has been linked to AZS phenotypes. Here, bi-allelic KIF9 loss-of-function variants were identified through whole-exome-sequencing of two unrelated individuals included in a cohort of 92 Chinese males exhibiting atypical sperm motility phenotypes. Both of these men exhibited typical AZS and suffered from infertility together with the complete absence of KIF9 expression. In contrast to these KIF9-deficient patients, positive KIF9 staining was evident throughout the flagella of sperm from normal control individuals. Immunoprecipitation analyses revealed that KIF9 was able to interact with the microtubule central pair (CP) component hydrocephalus-inducing protein homolog (HYDIN) in human samples. Consistently, KIF9 was undetectable in spermatozoa harboring CP deletions. The morphologicy of KIF9-deficient spermatozoa appeared normal under gross examination and transmission electron microscopy. Together, these findings indicate that KIF9 associates with the central microtubules in human sperm and that it functions to specifically regulate flagellar swinging. Like in mice, in vitro fertilization was sufficient to overcome the fertility issues for these two patients. Overall, these results offer greater insight into the biological functions of KIF9 in the assembly of the human flagella and its role in male fertility.